Integrating Ibn Khaldun’s Concept of Asabiyyah into Criminal Law to Address AI-Facilitated Violence Against Women - Martha, Aroma Elmina (Unisia, 2025)
This article examines the escalation of violence against women facilitated by artificial intelligence technologies in Indonesia and addresses the limitations of existing criminal law frameworks in responding to technology-facilitated gender-based violence. Its primary objective is to integrate Ibn Khaldun’s concept of asabiyyah, understood as social solidarity and collective responsibility, with modern criminal law in order to strengthen legal protection for women in the artificial intelligence era. Employing a normative juridical methodology, the study combines doctrinal legal analysis with a structured review of classical Islamic thought, contemporary legal theory, national legislation, international human rights instruments, and selected Indonesian cases of artificial intelligence-enabled sexual violence. The findings demonstrate that current legal instruments inadequately address artificial intelligence-generated harms due to definitional gaps, evidentiary challenges, and fragmented institutional responses, which often exacerbate victim vulnerability. Through the lens of asabiyyah, the article argues that effective protection requires not only formal legal reform but also the institutionalization of inclusive social solidarity that mobilizes communities, platforms, and state actors in prevention, reporting, and victim support. The analysis further proposes concrete reforms, including the recognition of artificial intelligence-generated content as a distinct criminal category, the strengthening of electronic evidence standards, and the establishment of community-based support mechanisms under state oversight. The study concludes that integrating Ibn Khaldun’s social theory with modern criminal law offers a culturally grounded and normatively robust framework for addressing artificial intelligence-facilitated violence against women, with significant implications for gender justice, legal reform, and ethical artificial intelligence governance in Indonesia.